PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KEPUASAAN KERJA KARYAWAN PADA PT POS INDONESIA CABANG CIPUTAT TANGERANG SELATAN - Chepyan Nursa’bani, Muhammad (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of workload and compensation on employee job satisfaction at PT. Pos Indonesia Ciputat Branch. This study uses a quantitative method with data collection techniques through the distribution of questionnaires and literature studies. The population in this study is 139 employees. The sample used was 58 employees using the Slovin technique. The data analysis used was validity test analysis, reliability test, classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, determination coefficient test and hypothesis test with the help of the SPSS 26 application. The results of this study show that: Regression equation Y = 21.766 + 0.549X1, correlation value of 0.638 means that the two variables have a strong relationship level. The value of the determination coefficient was 40.8%. The hypothesis test obtained a calculation of 3.776 > a table of 1.673 significant values of 0.000 < 0.05. Thus, Ho1 is rejected and Ha1 is accepted, meaning that there is a positive and significant influence of workload on employee job satisfaction. Compensation has a positive and significant effect on employee job satisfaction with the regression equation Y = 10.401 + 0.773X2, a correlation value of 0.653 means that the two variables have a strong relationship level. The value of the determination coefficient was 42.7%. The hypothesis test obtained a calculation of 4.073 > a table of 1.673 significant values of 0.000 < 0.05. Thus, Ho2 is rejected and Ha2 is accepted, meaning that there is a positive and significant influence of compensation on employee job satisfaction. Workload and compensation have a positive and significant effect on employee job satisfaction with the regression equation Y = 7.462 + 0.348X1 + 0.517X2, the correlation value is 0.738 meaning that the independent variable with the bound variable has a strong relationship level. The value of the determination coefficient was 54.5%. The hypothesis test obtained an F value of 32.927 > F table and a significant value of 0.000 < 0.05, then it can be concluded that Ho3 was rejected and H3 was accepted, meaning that there was a simultaneous positive and significant influence between workload and compensation on employee job satisfaction at PT Pos Indonesia Ciputat South Tangerang Branch.